Saltwater intrusion analysis in east coast of Terengganu using multivariate analysis (Analisis Pencerobohan Air Masin di Kawasan Pantai Timur, Terengganu Menggunakan Analisis Multivariat) - Muhammad Barzani, Gasim; Mohd Yusoff, Ibrahim; Azman, Azid (Malaysian Society of Analytical Sciences, 2016)
Coastal aquifer groundwater is vulnerable to saltwater contamination as it is located near the coastline. Therefore, a study is conducted to confirm all the major source of pollutants on coastal groundwater based on 13 sampling wells that located close to Terengganu coastline as well as to assess the intensity of saltwater intrusion into the wells. Measurements of selected water quality parameters such as dissolve oxygen (DO), electrical conductivity (EC), total dissolve solid (TDS), salinity, pH, turbidity and total suspended solid (TSS) were obtained from each well by using certified scientific instruments. Data were analysed by using multivariate techniques which involves principle component analysis (PCA) and cluster analysis (CA). CA was performed by using hierarchical agglomerative cluster analysis (HACA) technique. PCA yielded two PCs where PC1 forms composite factor loadings of TDS, salinity and EC that represented the saltwater intrusion meanwhile, PC2 formed composite factors of turbidity, TSS and TDS that represented the anthropogenic pollutions. CA successfully classified sampling wells into seven clusters; Extreme High (EH), Very High (VH), High (H), Moderate (M), Low (L), Very Low (VL) and Extreme Low (EL) where each cluster represented the saltwater intrusion intensity in decreasing order.